Social epidemiology of cardiometabolic risk factors in early adolescents - Jason M. Nagata; Christiane K. Helmer; Jennifer H. Wong; Seohyeong Lee; Sydnie K. Domingue; Patrick Low; Abubakr A.A. Al-shoaibi; Joan E. Shim; Kyle T. Ganson; Alexander Testa; Orsolya Kiss; Holly C. Gooding; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: To estimate associations between sociodemographic factors and cardiometabolic risk factors among a demographically diverse sample of U.S. adolescents aged 10–14 years. Methods: This study analyzed data from the Adolescent Brain Cognitive Development (ABCD) Study (N = 1412), Years 2 and 3 (2018–2021). Cardiometabolic risk factors including hemoglobin A1c and cholesterol (total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and non-HDL-C) were assessed. Multivariable linear regression models were conducted to estimate the associations between sociodemographic factors (age, sex, race and ethnicity, household income, and parental education) and cardiometabolic risk factors (hemoglobin A1c, TC, HDL-C, and non-HDL-C). Results: The average hemoglobin A1c level was 5.2 % (±0.4 %), the average TC level was 156.6 (±28.9) mg/dL, and the average HDL-C level was 56.0 (±12.9) mg/dL. Out of our sample, 0.5 % had diabetes (hemoglobin A1c ≥ 6.5 %), 7.6 % had high TC (≥200 mg/dL), and 7.4 % had low HDL-C (<40 mg/dL). Older age was associated with lower TC, HDL-C, and non-HDL-C levels. Male sex was associated with higher hemoglobin A1c (beta coefficient [B] 0.04; 95 % confidence interval [CI], 0.00, 0.08; p = 0.037) and lower TC (B −3.14; 95 % CI, −6.17, −0.11; p = 0.042) compared to female sex. Black and Native American race and ethnicity were associated with higher hemoglobin A1c compared to White race. Higher household income was associated with higher TC and HDL-C. Conclusion: This study of a diverse population of early adolescents identified sociodemographic differences in hemoglobin A1c and cholesterol levels that can inform clinical and public health interventions.